Quality Characteristics of Buffalo (Bubalus bubalis) Milk Candy as Affected by Different Ratios of Sucrose and Glucose Syrup as Humectant (Journal of Buffalo Science, 2025)
Background: This research evaluates the effect of the different proportions of sucrose and glucose syrup (100:0, 85:15, 70:30, and 55:45) on the overall quality of buffalo milk candy. The objective was to identify the optimal ratio that enhances both its microbial stability and sensory appeal. Methods: Buffalo milk candy was kept at room temperature, and samples were drawn for microbial testing, moisture, water activity (Aw), and sensory analysis. Results: A visible mold growth was observed in 100:0 (Day 30), 85:15 (Day 40), and 70:30 (Day 52), and therefore, other analyses were discontinued. Moisture content and Aw of all the treatments were significantly different throughout the storage period. However, with the increase in glucose syrup, Aw decreases consistently with time, thus enhancing the product's safety and stability. On the other hand, sensory evaluation did not show significant differences across all parameters in all treatments during the storage period. Conclusion: In conclusion, the addition of a higher proportion of glucose syrup, specifically 55:45, improved both the shelf-life and maintained the sensory quality of buffalo milk candy.